DETERMINAN KEPUTUSAN INVESTASI MAHASISWA PADA GALERI INVESTASI PERGURUAN TINGGI DI SURABAYA DAN MALANG - SALERINDRA, BAGAS (Jurnal Ilmu Manajemen (JIM), 2019)
This study aims to determine the influence of the independent variables (financial literacy, accounting information, illusion of control, risk tolerance, risk perception, overconfidence, and herding) on the dependent variable (investment decision) in college students who have investment galleries in Surabaya and Malang. This study is a causality study with quota sampling. The data of this study is quantitative by collecting data by questionnaire. The data analysis technique used is multiple linear regression. The results of this study based on t statistical tests show that accounting information and risk tolerance have a negative effect on investment decisions variables. Risk perception have a positive effect on investment decisions. While thevariables financial literacy, illusion of control, overconfidence, and herding did not affect investment decisions. Based on the statistical test f, all independent variables simultaneously influence the dependent variable (investment decision). Keywords: determinant investment; investment decisions; college students; investment galleries.